Psychosis and temporal lobe epilepsy-role of electroconvulsive therapy - Anderson, Naomi Mifflen (BMJ Publishing Group, 2012)
A 49-year-old female presented for admission with features of being withdrawn, inability to comprehend questions, auditory hallucinations and disorganised thoughts. She also had a previous diagnosis of temporal lobe epilepsy. She did not respond well to psychotropic medications. During her sleep deprived EEG, she had a brief episode of seizures. Following this, she showed improvement in psychosis for a day or so. Based on this finding, it was decided to initiate a course of electroconvulsive therapy. She improved remarkably on six treatments. At the time of discharge, she was in a stable condition.